Cadmium in tobacco smokers: a neglected link to lung disease?. (28th March 2018) - Ganguly, Koustav; Levänen, Bettina; Palmberg, Lena; Åkesson, Agneta; Lindén, Anders
Cadmium in tobacco smoke may contribute to the development of pulmonary emphysema. However, there is poor understanding of the mechanisms behind the pathogenic role of cadmium in this and other smoking-related lung diseases. The traditional focus on the total body burden of cadmium, estimated through analysis of urine, may not fully reflect the local burden of cadmium, since it is inhaled by smokers. Thus, assessing the local accumulation of cadmium in the lungs appears more relevant, given that there is tissue-specific retention of cadmium. In this review, we outline the principal sources of cadmium exposure and the clinical effects of occupational exposure. In addition, we review evidence on local cadmium and its association with alterations in innate immunity in tobacco smokers. Moreover, we scrutinise the data on cadmium as a cause of lung disease in translational models. We conclude that cadmium may contribute to smoking-related lung diseases, possibly via an altered redox balance and by making macrophages dysfunctional. However, there is a need for new studies on local cadmium levels and their relation to pathology in long-term tobacco smokers, as well as for more in-depth studies on cellular and molecular mechanisms, to elucidate the importance of cadmium in smoking-related lung diseases. Cadmium in tobacco smoke emerges as a potentially important pathogenic factor in smoking-related lung disease http://ow.ly/msOm30irmg7